La fabrique des saints - Jean-Robert Armogathe (Mélanges de la Casa de Velázquez, 2003)
In 1622, Isidore the Farmer, Ignatius Loyola, Francis Xavier and Teresa of Avila were all endowed with sainthood (at the same time as Filippo Neri). This article examines the sanctification procedure through the cases of some Spanish saints: the social and political importance of models of sainthood in the 17th and 18th centuries invites discussion of the regulatory measures introduced by Urban VIII. The glamour of sainthood is the outcome of complex procedures involving experts in civil and canon law, theologians and physicians. The Catholic church seeks to retain its independence of decision and freedom of judgment in the face of external pressures exerted in favour of national causes. The De servorum Dei beatificatione of Pope Lambertini (Benedict XIV, d. 1758) provides a good basis for assessment of the significance and the goals of the fabrique des saints in the modern age.